Strategi Keberlanjutan Inovasi Daerah di Kabupaten Pelalawan - Azhar Riady; Deswanisa Fajriana; Tengku Ritawati (Research and Development Agency Ministry of Home Affairs, 2026)
The sustainability strategy of regional innovation is a crucial aspect that determines whether innovation achievements can be maintained consistently from year to year. Existing studies have largely examined innovation sustainability through external prerequisites such as leadership commitment from regional heads and a conducive policy ecosystem, which have proven effective in regions with well-established governance. However, not all local governments operate under such conditions: some face limited leadership support and the absence of regulations that systematically encourage innovation. At the same time, innovation sustainability strategies from the perspective of BRIDA as the innovation coordinator remain rarely explored. This study offers an alternative by analyzing how BRIDA of Pelalawan Regency implements innovation sustainability strategies in responding to the dynamics of the Regional Innovation Index (IID) assessment during 2021-2024. One key challenge is the eligibility time limit for innovation reporting, which only covers the most recent two years, requiring continuous renewal of the innovation portfolio. This study employs a qualitative methodology with data collected through documentation of IID reports, strategic planning documents, and innovation reporting statistics. Findings reveal that BRIDA Pelalawan Regency applies four integrated strategies: independent projection analysis based on assessment weights, expansion of reporting work unit coverage, innovation mentoring, and development of existing innovations. Implementation of these strategies successfully increased Pelalawan Regency’s IID score consistently from 47.33 in 2021 to 65.70 in 2024, leading Pelalawan Regency to achieve the highly innovative predicate while maintaining second rank in Riau Province. This study provides a practical contribution as a reference for BRIDA in other regions in designing innovation sustainability strategies that are adaptive to the dynamics of national IID assessment.